To simplify \( \frac{4^{13}}{3^{-5}} \), we can first rewrite the expression. Dividing by \( 3^{-5} \) is equivalent to multiplying by \( 3^{5} \):
\[ \frac{4^{13}}{3^{-5}} = 4^{13} \cdot 3^{5} \]
Now, we can leave it in this form or calculate the numerical value of each term:
Calculating \( 4^{13} \): \[ 4^{13} = (2^2)^{13} = 2^{26} \]
So the expression becomes: \[ 2^{26} \cdot 3^{5} \]
The final simplified form is: \[ \frac{4^{13}}{3^{-5}} = 4^{13} \cdot 3^{5} = 2^{26} \cdot 3^{5} \]
This is the simplified form of the expression. If you need a numerical value, you can calculate that as well:
\[ 2^{26} = 67108864 \quad \text{and} \quad 3^5 = 243 \]
Thus: \[ 2^{26} \cdot 3^{5} = 67108864 \cdot 243 = 162841573940 \]
So \( \frac{4^{13}}{3^{-5}} = 2^{26} \cdot 3^{5} = 162841573940 \) if a numerical value is required.